THE SCOPE OF DATA CONSIDERED AS MEDICAL CONFIDENTIALITY AND BASIC REQUIREMENTS FOR PATIENT CONSENT TO MEDICAL INTERVENTION - Ghukasyan, Shushanik; Abgaryan, Izabel (State and Law, 2025)
This article examines the legal definition of the term "medical confidentiality" and identifies the key scope of information considered as medical confidentiality. It argues that medical confidentiality encompasses not only data about a person’s health status but also information related to seeking and receiving medical care, which may include personal and private life details. Health-related data involves all information regarding the patient’s past, present, or future physical or mental health condition. Additionally, data obtained during the process of seeking or receiving medical care can cover a wide range, including the patient’s personal, family, professional, economic, and financial circumstances, as well as relationships with other individuals. The article also outlines the main conditions for the lawful transfer of data considered as medical confidentiality. In terms of patient consent three prerequisites are identified for determining the presence of informed consent for medical intervention: competence, the availability of necessary information, and voluntariness. Each of these components is thoroughly analyzed within the article.